Critical Histories, Native Christianities, and Self-Determination Beyond the First Amendment: Trends in Native American Religious Studies - Waters, James W (Indigenous Religious Traditions, 2024)
This article highlights five books published in the last five years that address questions of Native American self-determination, religion, law, and Empire. These texts provide a window into three clusters of questions and issues driving much contemporary scholarship on Native American religious traditions. First, Wenger and Johnson’s (2022) edited volume provides a diverse exploration of Empire’s role in shaping American Indian identities post-contact. Second, Schermerhorn (2019) and Woodley (2022) provide two accounts of how some Native Americans make Christianity their own through indigenous applications, practices, and (re)interpretations. Last, I examine McNally (2020) and Lloyd (2024), two books on Native American religious freedom and law that provide differing perspectives on the possible future of Native resistance in US courts. I argue that the single thread that runs through these works is a desire to identify the most helpful and effective resistance strategies for Native self-determination in the context of white settlerism. Each author believes religion plays some role in said self-determination process, although there is disagreement about what that role is or ought to be.